Analysis on Chemical Reaction Kinetics for Phosphorus Removal of Sewage in Horizontal Subsurface Flow Constructed Wetlands - Wang, Hao; Yang, Zhinian; Liu, Bo; Li, Xuejin (Asian Journal of Chemistry, 2014)
Different subsurface flow constructed wetlands were adapted to advanced treat sewage treatment plant secondary effluent and analyze the effect of phosphorus removal and its reaction kinetics model. The results showed that horizontal subsurface flow wetland removal of phosphorus in sewage exhibited a good removal characteristic and compared with horizontal zeolite wetland, horizontal limestone wetland exhibited better phosphorus removal effect, the removal rate basically retained at 66.3 ± 3.32 to 92.0 ± 4.82 %. In addition, based on the reaction dynamics simulation analysis, the results showed that two subsurface flow wetlands were in line with the characteristics of first-order kinetics equation, i.e. phosphorus removal process was basically carried out to a reaction.